Comparative study of structural steeland reinforced concrete method : a project management case study - Hu, Wei Kiet. (Universiti Malaysia Sarawak (UNIMAS), 2004)
Structural steel construction has been quite common construction method in the world. In other developed countries such as Japan, structural steel is considered as a norm and is frequently opted for in construction. However, in Malaysia, steel construction is one of the construction methods, which is yet to be as popular. Many of our traditional construction methods such as reinforced concrete construction are still greatly favoured by our construction industry. One of the common comment of the usage of structural steel in construction is it is a more expensive option if compared to RC construction. It is the aim of this research study to carry out a comparative study between structural steel construction method with one type of traditional construction method (RC construction is chosen here). Comparison will be made with 3 principle project management criteria for a successful project, i.e. time, cost and quality. Through this case study on these two type of construction methods, the advantages and weaknesses of stee1 construction can be reviewed. It was found that material cost for the structural steel construction method is indeed more expensive than the RC construction method and this is because focus is on the material cost only and other perspectives such as quality; time savings and cost savings, which may result; are generally ignored. From this study, it is hope that structural steel usage can be strengthened and other aspects such as time savings and quality can be taken into more serious consideration by all parties in the industry when choosing construction method to adopt. And hopefully, structural steel can be as good as option if not a better one compared to R.C construction.